Frequency and variation of neural tube defects at Liaquat University Hospital Jamshoro, Sindh, Pakistan - Goswami, Pushpa; Memon, Samreen; Khimani, Vashdev; Rajpar, Farhana (International Journal of Research in Medical Sciences, 2017)
Background: Neural tube defects (NTDs) are a group of congenital malformations of the neural tube. The incidence of NTDs in Pakistan is 13.90 per 1000 deliveries. Such type of study in our setup is conducted for the first time which shows that different varieties of (NTDs) are seen commonly in our setup also. Methods: This descriptive study was conducted in department of Neurosurgery of Liaquat University Hospital Jamshoro, Sindh Pakistan with collaboration of department of Anatomy of Liaquat University of Medical and Health Sciences Jamshoro to determine the frequency and variations of neural tube defects seen in this institution. 45 patients with (NTDs) were included in the study. Out of 45 patients 18 were males and 27 were females. All were admitted through the outpatient department. The type of anomaly was recorded with other bio data. Results: In this study Hydrocephalous accounts for 25 cases (55.5%), hydrocephalus with meningocele in 01 case (2.2%) and hydrocephalus with encephalocele in 02 cases (4.4%) in addition is seen. Myelomeningocele seen in 04 cases (8.8%), Meningocele in 06 cases (13.3%), congenital dermal sinus and dandy walker syndrome 01 (2.2%) cases of each, also seen in this study 01 cases of Lipomyelocele with mengiocele and 01 case of Encephalocele with microcephaly which accounts for 2.2% of all neural tube defects. Conclusions: The high occurrence of NTDs observed in this study calls for a special attention. A nationwide surveillance can recognize the disease burden in pre & post-natal period and related risk factors to plan future strategies for prevention, early diagnosis and timely management.